Primary care physicians' use of the proposed classification of common mental disorders for ICD-11. (4th May 2017) - Goldberg, David P; Lam, Tai-Pong; Minhas, Fareed; Razzaque, Bushra; Robles, Rebeca; Bobes, Julio; Iglesias, Celso; Fortes, Sandra; Mari, Jair de Jesus; Gask, Linda; García, José Ángel; Dowell, Anthony C; et al.
Abstract: Background: The World Health Organization is revising the classification of common mental disorders in primary care for ICD-11. Major changes from the ICD-10 primary care version have been proposed for: (i) mood and anxiety disorders; and (ii) presentations of multiple somatic symptoms (bodily stress syndrome). This three-part field study explored the implementation of the revised classification by primary care physicians (PCPs) in five countries. Methods: Participating PCPs in Brazil, China, Mexico, Pakistan and Spain were asked to use the revised classification, first in patients that they suspected might be psychologically distressed (Part 1), and second in patients with multiple somatic symptoms causing distress or disability not wholly attributable to a known physical pathology, or with high levels of health anxiety (Part 2). Patients referred to Part 1 or Part 2 underwent a structured diagnostic interview. Part 3 consisted of feedback from PCPs regarding the classification. Results: In Part 1, anxious depression was the most common disorder among referred patients. PCPs assigned the highest severity ratings to anxious depression, and the next highest to current depression; current anxiety was rated as least severe. Considerable overlap was found between bodily stress syndrome (BSS) and health anxiety (HA). The psychiatric interview recorded higher rates of mood and anxiety disorders diagnoses among patients with BSS than did PCPs. PCPs' satisfaction with the revised classification was high. Conclusions: Results generally supported the inclusion of the new categories of anxious depression, BSS and HA for ICD-11 PHC and suggested that PCPs could implement these categories satisfactorily.